Epidemiological Situation of Necrotizing Fasciitis and Factors in Thailand and Factors Associated with Its Morbidity and Mortality, 2014–2018 - Tantirat P; Rattanathumsakul T; Praekunatham H; Pachanee K; Suphanchaimat R (Dove Medical Press, 2020)
Panupong Tantirat,1 Thanit Rattanathumsakul,1 Hirunwut Praekunatham,2 Kumaree Pachanee,3 Repeepong Suphanchaimat1,3 1Division of Epidemiology, Department of Disease Control, Ministry of Public Health, Thailand; 2Division of Occupational and Environmental Diseases, Department of Disease Control, Ministry of Public Health, Nonthaburi, Thailand; 3International Health Policy Programme, Ministry of Public Health, ThailandCorrespondence: Panupong TantiratDivision of Epidemiology, Department of Disease Control, Ministry of Public Health, Building 10, Floor 3, 88/21 Tiwanon Road, Talat Khwan Subdistrict, Mueang District, Nonthaburi 11000, ThailandTel +66 878190796Fax +66 2 5918581Email golftppanupong@gmail.comIntroduction: Necrotizing fasciitis (NF) is a rare skin and soft-tissue bacterial infection with high morbidity and mortality. Knowledge about the prevalence and incidence of NF in Thailand is quite sparse. The objective of this study was to determine the prevalence of NF in Thailand and factors that may be potentially associated with NF morbidity and mortality.Methods: A cross-sectional study using secondary data from Thailand’s national health databases between 2014 and 2018 was conducted. Descriptive statistics using median and percentage formats were used. This was complemented by multivariable logistic regression to determine the association between various factors (such as age and underlying diseases) with NF morbidity and mortality. Univariate spatial data analysis was exercised to identify the geographical hot spots in which the disease appeared.Results: During 2014– 2018, we found 90,683 NF cases. About 4.86% of the cases died. The median age for all cases was 59.39 years old. The annual incidence of NF demonstrated an upward trend (from 26.08 per 100,000 population in 2014 to 32.64 per 100,000 population in 2018). The monthly incidence was highest between May and August. A high incidence cluster (as indicated by local Moran’s I) was found in the north-eastern region of Thailand. The most infected sites were on the ankles and feet (43.18%) with an amputation rate of 7.99% in all cases. Multivariable logistic regression indicated that the significant risk factor for amputation was a presence of underlying diseases, namely diabetes (OR 7.94, 95% CI 7.34– 8.61). Risk factors for mortality included being elderly (OR 1.82, 95% CI 1.68– 1.98) and a presence of underlying hypertension (OR 1.16, 95% CI 1.07– 1.27), cirrhosis (OR 4.67, 95% CI 4.17– 5.21), and malignancy (OR 1.88, 95% CI 1.55– 2.26).Discussion and Conclusion: As the elderly and those with chronic underlying diseases are likely to face non-preferable health outcomes from NF, healthcare providers should pay great attention to these groups of patients. Early and intensive treatment might be considered in these groups of patients. Further studies that aim to validate the volume of actual NF cases and reported NF cases are recommended.Keywords: necrotizing fasciitis, incidence, mortality, morbidity